Respuesta :

[tex]\huge\mathscr{\colorbox{blue}{\color{yellow}{Answer:}}}[/tex]

[tex]\large{\rightarrow{6\:(x\:+\:4)\:=\:-\:2\:(4x\:-\:4)\:+\:8x}}[/tex]

[tex]\large{\rightarrow{6\:(x\:+\:4)\:=\:-\:2\:(4x\:-\:4)\:+\:8x}}[/tex]

[tex]\large{\rightarrow{6x\:+\:24\:=\:-\:8x\:+\:8\:+\:8x}}[/tex]

[tex]\large{\rightarrow{6x\:+\:24\:=\:{\cancel{-\:8x}}\:+\:8\:+{\cancel{\:8x}}}}[/tex]

[tex]\large{\rightarrow{6x\:+\:24\:=\:8}}[/tex]

[tex]\large{\rightarrow{6x\:=\:8\:-\:24}}[/tex]

[tex]\large{\rightarrow{6x\:=\:16}}[/tex]

[tex]\large{\rightarrow{x\:=\:\frac{-\:16}{6}}}\\[/tex]

[tex]\large\pink{\boxed{\color{lime}{\rightarrow{x\:=\:\frac{-\:8}{3}}}}}\\[/tex]